Supersessionist or Complementary? Reassessing the Nature of Legal Revision in the Pentateuchal Law Collections - Berman, Yehoshuʿa (Journal of Biblical literature, 2016)
Scholars studying the evolution of the biblical law corpora are today divided into two camps. One camp argues that the authors of these corpora revised earlier law collections with the aim of superseding them. A growing countermovement has challenged the classical paradigm. This camp maintains that, as biblical authors revised an earlier code, they did not reject the authority and standing of the earlier collection. Rather, they viewed their own literary works as complements to the earlier ones. Scholars routinely adopt one position or the other and demonstrate how that position produces constructive readings of the passages at hand. One is hard put, however, to find studies that systematically set the methodological claims of each camp in conversation with each other to measure and mediate the validity of these respective approaches. This study seeks to remedy this situation. In considering the positions of the two camps, I emphasize how each relates to five critical issues: the ubiquitous use of lemmatic citation; their respective understanding of the reasons for the redaction of the Pentateuch; the ubiquitous blending of legal materials elsewhere in the Hebrew Bible; a consideration of the legal terminology and models each uses to assess the texts; and the phenomenon in Deuteronomy of cross-referencing other legal sources. With these underpinnings revealed, I assess each position, concluding that the complementarian position held by the more recent camp is the more cogent of the two.